Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1108/17410401211249201
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting project performance considering the influence of leadership style on organizational agility

Abstract: Purpose -The purpose of this paper is to analyze the influence of leadership style and factors associated with organization agility on project performance. Design/methodology/approach -It is a case study carried out at a leading corporation driven towards innovation projects. Literature on this subject seems to be mainly focused on the contribution of processes and strategies that lead to agility, and few cases report the influence of people and leadership style on this factor. Upon analysis, a proposed charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
(12 reference statements)
3
18
0
Order By: Relevance
“…On the contrary, the absence of required leadership competencies can result in augmentation of adversities that may lead to a decline in the project performance. The respective findings were found in alignment to a mixed-mode study conducted by Aurélio de Oliveira, Veriano Oliveira Dalla Valentina [ 74 ] on 32 highly skilled and influential project managers in the field of R&D; who have served various forms globally. The correlational study depicted a possibly potential impact of an appropriate leadership approach to resolve organizational situations and deliver targeted performance.…”
Section: Discussionsupporting
confidence: 73%
“…On the contrary, the absence of required leadership competencies can result in augmentation of adversities that may lead to a decline in the project performance. The respective findings were found in alignment to a mixed-mode study conducted by Aurélio de Oliveira, Veriano Oliveira Dalla Valentina [ 74 ] on 32 highly skilled and influential project managers in the field of R&D; who have served various forms globally. The correlational study depicted a possibly potential impact of an appropriate leadership approach to resolve organizational situations and deliver targeted performance.…”
Section: Discussionsupporting
confidence: 73%
“…Through leadership the employees can be directed to the achievement of OA. The results of previous empirical studies (Aurélio de Oliveira et al, 2012;Karimi et al, 2016;Raeisi & Amirnejad, 2017;Veiseh et al, 2014) indicated that leadership positively influenced the OA. It can be interpreted that the improvement of EL will affect the improvement of OA.…”
Section: Discussionmentioning
confidence: 90%
“…de Oliveira et al (2012) conducted an empirical study to analyze the influence of leadership style and factors associated with organization agility on project performance. Their main finding was that the combination of all these elements yields the highest project performance (de Oliveira et al , 2012, p. 653).…”
Section: Agile Leadershipmentioning
confidence: 99%
“…de Oliveira et al (2012) conducted an empirical study to analyze the influence of leadership style and factors associated with organization agility on project performance. Their main finding was that the combination of all these elements yields the highest project performance (de Oliveira et al , 2012, p. 653). The analysis carried out in this study confirms the intuition, expressed by scholars and business leaders alike, that top-down, disciplinarian style leadership is neither appropriate nor conducive to collaboration and innovation (Hamel, 2009).…”
Section: Agile Leadershipmentioning
confidence: 99%
See 1 more Smart Citation